Reducing the CARICOM food import bill and the real cost of food : policy investment and options - Silva, Sacha [et al] (FAO/UN Port of SpainTT, 2011)
Analyses the composition and policy options surrounding the food import bill (FIB) of the CARICOM Member States, as well as policy options for its reduction.